Prenatal Maternal and Possible Transgenerational Epigenetic Effects on Milk Production - Gudex, Boyd (Public Library of Science, 2014)
This study investigated whether the prenatal maternal environment in dairy cattle influences the postnatal milking performance of the resulting daughters and grand-daughters. Linear mixed models were used to analyse whole season milk production from ∼46000 Jersey and ∼123000 Holstein Friesian cows in their 1(st) and 2(nd) lactations. Variation in the prenatal environment was associated with a small but significant (P<0.05) proportion of the total phenotypic variation (0.010 to 0.015) in all traits in Holstein Friesian cows and in the first lactation milk volume (0.011) and milk protein (0.011), and the second lactation milk fat (0.015) in the Jersey breed. This indicates that the prenatal environment does influence the adult performance of the subsequent daughter. Associations between daughter performance and dam and grand-dam traits indicative of their prenatal environment were also estimated. A one litre increase in the dam’s herd test milk volume was associated with a 7.5 litre increase in the daughters’ whole season milk yield and a 1% increase in either the dams’ herd test milk fat or protein percentage was associated with a reduction in daughter whole season milk volume (−49.6 and −45.0 litres for dam fat and protein, respectively). Similar results between the grand-dam herd test traits ansd the daughters’ whole season milk production were observed with a 1% increase in either grand-dam milk fat or protein percentage associated with a reduction in daughter whole season milk yield (−34.7 and −9.7 litres for fat and protein, respectively). This study revealed that the prenatal environment of the dam and the grand-dam can influence milk production in the subsequent daughters, though the effects are small. The similarity of the results between the dam daughter and the grand-dam daughter analyses suggests that the majority of the prenatal maternal effects are mediated by epigenetic mechanisms.